PP42 Are we squeezing the pips? Financial austerity and disinvestment in low clinical value procedures in England: a time-trend analysis. (2nd September 2014) - Coronini-Cronberg, S; Bixby, H; Laverty, AA; Millett, C
Abstract : Background: The recent global financial crisis has precipitated a tightening of health budgets in many countries, including England. In 2009, the National Health Service (NHS) was ordered to make £15 to £20 billion recurrent efficiency savings between 2011 and 2014, a cumulative saving of 17%. The savings were to be derived through improvements in service quality and efficiency, including reducing the provision of 'low value procedures', that is interventions that are inefficient, over-used or inappropriate. We examined whether selected low value procedures declined in the first year of financial cuts (i.e. 2011/12), and whether any reductions were equitable. Methods: We performed a negative binomial regression analysis of routinely-collected Hospital Episode Statistics data covering 2002/03 to 2011/12. Changes in the surgical procedure rate were examined in the first year of efficiency savings after taking the underlying trend into account. Definitions of low value procedure are inconsistent, so a pragmatic review of commonly targeted procedures plus a consensus exercise resulted in the following eight elective interventions being analysed: cataract surgery; inguinal hernia repair; hysterectomy for heavy menstrual bleeding; spinal surgery for lower back pain; myringotomy; primary hip replacement; coronary revascularisation; and gall bladder removal. The latter two were designated control procedures. Results: The final sample comprised 5, 277, 980 admissions for the eight procedures. The first year of efficiency savings coincided with significant declines: -4.8% (95% CI: -3.0% to -6.6%) in cataract surgery; -10.7% hysterectomies (95% CI: -1.0% to 1–9.5%); and -11.4% myringotomies (95% CI: -2.7% to -19.3%). The control group showed no change. In terms of equity, a mixed picture emerged. In 2011/12, the rate of cataract surgery fell by a similar level in all deprivation groups; by contrast the rate of hip replacements only fell significantly in the least deprived group (-6.3%; 95% CI: -2.2% to -10.3%). Conclusion: Our study suggests there is evidence of significant disinvestment in some procedures of low clinical value since the advent of the efficiency savings imposed on the English NHS in 2011/12, including cataract surgery, hysterectomies for heavy menstrual bleeding, and myringotomies. This suggests commissioners could be making efforts to achieve efficiency savings by funding fewer procedures of low clinical value. However, our analysis also highlights that magnitude of any reductions can vary across deprivation groups, suggesting a need to ensure disinvestment is applied equitably across the population.